Influence of a biliary stent in patients with advanced pancreatic cancer treated with modified FOLFIRINOX. Issue 49 (9th December 2022) - Yoshikawa-Kimura, Akie; Taira, Koichi; Maruyama, Hirotsugu; Ishikawa-Kakiya, Yuki; Yamamura, Masafumi; Tanoue, Kojiro; Hagihara, Atsushi; Uchida-Kobayashi, Sawako; Enomoto, Masaru; Kimura, Kenjiro; Tanaka, Shogo; Amano, Ryosuke; et al.
Abstract : Endoscopic biliary drainage is the recommended 1 st -line treatment for malignant biliary obstruction. Although a high incidence of febrile neutropenia has been reported in patients treated with FOLFIRINOX and a biliary stent, it remains unknown whether the biliary stent contributes to patient survival. Thus, we aimed to elucidate the effects of biliary stents on the survival of patients with advanced pancreatic cancer treated with modified FOLFIRINOX (mFFX). We retrospectively reviewed medical charts of patients with advanced pancreatic cancer treated with mFFX between January 2014 and April 2020. We compared the overall survival (OS) of patients with and without biliary stent during mFFX treatment and examined the independent effect on mortality using propensity score matching. Overall, we included 89 patients (stent group, n = 24; non-stent group, n = 65). The proportion of patients with pancreatic head cancer was significantly higher in the stent group than in the non-stent group ( P  < .01). Stratification analysis in patients with pancreatic head cancer revealed that OS was significantly shorter in the stent group than in the non-stent group ( P  = .03). After propensity score matching, 19 pairs of patients in each group were analyzed. The stent group revealed a significantly shorter survival than the non-stent group (median OS, 10.3 vs 24.9 months; P  < .01). The incidences of febrile neutropenia ( P  = .01) and biliary tract-related events that required biliary stenting or stent replacement ( P  < .01) were significantly higher in the stent group than in the non-stent group. Stent insertion was an independent risk factor for overall mortality. Biliary stents may reduce survival in patients with advanced pancreatic cancer. The rate of febrile neutropenia was higher in the stent group than in the non-stent group. There is a need to assess the patient's condition with discretion and develop a treatment strategy with short prognosis in mind after stent insertion.